A water-microorganism detecting device with freeform lens. (December 2018) - Wu, Heng; Zhang, Xianmin; Zhao, Genping; Cheng, Lianglun; Yu, Jindong; Ge, Peng
Highlights: A device for detecting the microorganisms in water with a freeform lens is developed. The freeform lens is designed with a predefined light intensity distribution. The device can realize a uniform illumination at the arbitrary depth of water. The device is compact and portable, and enjoys a high optical efficiency. The device possesses excellent performances and wide potential applications. Abstract: A device for detecting the microorganisms in water with a freeform lens is developed. The main components of the device include a water channel, a light-emitting diode (LED) light source, and a freeform lens. The freeform lens which plays a key role in the device is designed with a predefined light intensity distribution using a double freeform surface design method. Different from the traditional methods, during the construction of the lens, the mapping is established by an incident-emergent angle relation. As an example, a model of the device is designed. Monte Carlo ray tracing simulations are implemented to verify optical performance of the device. Installation error analyses on the LED source are also conducted. The results demonstrate that the device can generate a uniform illumination pattern at the arbitrary depth of the water and is feasible for the microorganism detection in water. Additionally, the results also show that the lens can achieve the uniform illumination without the influence of the illumination distance. An optical efficiency greater than 82% is obtained for the designed model.